DIGITAL MARKETING SEBAGAI METODA ALTERNATIF WIRAUSAHA BAGI MAHASISWA DI UNIVERSITAS NEGERI PADANG - Muhammad Adri; Hanesman Hanesman; Titi Sriwahyuni; Almasri Almasri (Universitas Negeri Padang, 2019)
Digital technology and the internet have opened opportunities for people to develop social interaction through this technology, with the birth of web technology, media and social networks, which led to the industrial revolution 4.0. This technology presents a new trend in building a business called Digital Marketing (DM). DM provides new opportunities for anyone to do entrepreneurship without being limited by time, place and region. More than a decade of entrepreneurship has become the focus of attention of the government in Education, as one of the ways to reduce national unemployment. Universitas Negeri Padang (UNP) answers the entrepreneurship education policy by making Entrepreneurship as a compulsory subject, promoting entrepreneurial student programs and integrated service units for career guidance and entrepreneurship. This paper examines more deeply how DM can be used as an alternative method of entrepreneurship for UNP students, which has direct touching student life as a millennial generation. The experimental method is used to see of improvement the knowledge and skills of students in DM through DM Training and Development of DM eLearning Resources (DMLR). To measure the success of the program, instruments were developed before and after training, as well as a questionnaire to assess the results of the DMLR development. The results of this study showed an increase in student knowledge and skills in DM and a good assessment of the developed DMLR.